In Situ Reverse Transcriptase-Nested Polymerase Chain Reaction to Identify Intracellular Nucleic Acids without the Necessity of Dnase Pretreatment and Hybridisation - Mario Menschikowski; Margot Vogel; Rolf Eckey; Gerd Dinnebier; Werner Jaross (Analytical Cellular Pathology)
In the present study a protocol of in situ reverse transcriptase‐nested polymerase chain reaction (in situ RT‐nested PCR) was examined based on the following modifications. (i) To exclude false positive signals caused by “DNA repair mechanisms” and “endogenous priming”, a two‐step PCR was applied after reverse transcription. The first step was performed in the presence of extrinsic primers and unlabeled nucleotides with a maximum of PCR cycles possible without destroying the cell morphology. The second step consisted of only one annealing/elongation reaction, the target sequence marked by addition of digoxigenin‐labeled nucleotides and intrinsic primers. (ii) In order to prevent amplifications of genomic DNA nested primer pairs were applied crossing intron sequences. (iii) To minimize the diffusion of PCR products in cells, the extrinsic primers were extended with complementary 5′‐tails. This approach results in the generation of high molecular weight concatamers during PCR cycles. By applying this protocol, immunostainings specific for phospholipase A2 of type IIA mRNA were exclusively detectable in the cytoplasm of HepG2 hepatoma cells, which were used as a model system, whereas the nuclei were unstained. Multiple control experiments yielded completely negative results. These data suggest that the in situ RT‐nested PCR, which in comparison to the method of in situ RT‐PCR‐in situ‐hybridisation is simpler and less time‐consuming, can be used as an alternative approach to identify intracellular nucleic acids.